The physique of elite female artistic gymnasts: A systematic review - Bacciotti, S.; Baxter-Jones, A.; Gaya, A.; Maia, J. (Journal of Human Kinetics, 2017)
It has been suggested that successful young gymnasts are a highly select group in terms of the physique. This review summarizes the available literature on elite female gymnasts` anthropometric characteristics, somatotype, body composition and biological maturation. The main aims were to identify: (i) a common physique and (ii) the differences, if any, among competitive/performance levels. A systematic search was conducted online using five different databases. Of 407 putative papers, 17 fulfilled all criteria and were included in the review. Most studies identified similar physiques based on: physical traits (small size and low body mass), a body type (predominance of ecto-mesomorphy), body composition (low fat mass), and maturity status (late skeletal maturity as well as late age-at-menarche). However, there was no consensus as to whether these features predicted competitive performance, or even differentiated between gymnasts within distinctive competitive levels. In conclusion, gymnasts, as a group, have unique pronounced characteristics. These characteristics are likely due to selection for naturally-occurring inherited traits. However, data available for world class competitions were mostly outdated and sample sizes were small. Thus, it was difficult to make any conclusions about whether physiques differed between particular competitive levels.